The Energetic 2022 Seismic Unrest Related to Magma Intrusion at the North Mid‐Atlantic Ridge - S. Cesca; M. Metz; P. Büyükakpınar; T. Dahm (Geophysical Research Letters, 2023)
Abstract A seismic swarm affected the 53.3°–54.3° Latitude North section of the Mid‐Atlantic Ridge from 26 September to 10 December 2022. We rely on regional, teleseismic and array data to relocate 61 hypocenters and derive 77 moment tensors. The 2022 swarm released a cumulative moment equivalent to Mw 6.3. Seismicity was shallow (7 ± 3 km depth). Most earthquakes are located along the ridge axis with typical, NS oriented normal faulting mechanisms, but a few among the largest and latest earthquakes have unusual thrust mechanisms and locations as far as ∼25 km from the ridge. We attribute the swarm to a shallow magmatic intrusion, with a vertical dike first propagating ∼60 km along axis, accompanied by shallow normal faulting, and then thickening and triggering thrust earthquakes off the ridge, in response to compressive stress buildup. The unrest provides a rare example of an energetic, magmatic driven swarm episode at the mid‐ocean ridge.